Structure and functional interaction of the extracellular domain of human GABA(B) receptor GBR2 - Geng, Yong (2012)
Inhibitory neurotransmission is mediated primarily by GABA. Metabotropic GABA(B) receptor is a G protein coupled receptor central to mammalian brain function. Malfunction of GABA(B) receptor has been implicated in a number of neurological disorders. GABA(B) receptor functions as a heterodimeric assembly of GBR1 and GBR2 subunits, where GBR1 is responsible for ligand-binding and GBR2 is responsible for G protein coupling. Here we demonstrate that the GBR2 ectodomain directly interacts with the GBR1 ectodomain to increase agonist affinity by selectively stabilizing the agonist-bound conformation of GBR1. We present the crystal structure of the GBR2 ectodomain, which reveals a polar heterodimeric interface. We also identify specific heterodimer contacts from both subunits, and GBR1 residues involved in ligand recognition. Lastly, our structural and functional data indicate that the GBR2 ectodomain adopts a constitutively open conformation, suggesting a structural asymmetry in the active state of GABA(B) receptor that is unique to the GABAergic system.